Formation and biological role NO at an allergic inflammation - O. V. Kozina; L. M. Ogorodova (Бюллетень сибирской медицины)
In the review ways and mechanisms of formation nitric oxide are considered. Effects metabolite nitric oxide in regulation of an allergic inflammation are analysed. The modern given participations nitric oxide in formation oxidative and nitrosative stresses, in regulation of the basic endocellular alarm ways, to realizations pro-and antiapoptosis effects.